2024
DOI: 10.1038/s41598-024-59942-3
|View full text |Cite
|
Sign up to set email alerts
|

Experience-dependent glial pruning of synaptic glomeruli during the critical period

Nichalas Nelson,
Dominic J. Vita,
Kendal Broadie

Abstract: Critical periods are temporally-restricted, early-life windows when sensory experience remodels synaptic connectivity to optimize environmental input. In the Drosophila juvenile brain, critical period experience drives synapse elimination, which is transiently reversible. Within olfactory sensory neuron (OSN) classes synapsing onto single projection neurons extending to brain learning/memory centers, we find glia mediate experience-dependent pruning of OSN synaptic glomeruli downstream of critical period odora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 100 publications
(162 reference statements)
0
0
0
Order By: Relevance
“…Given that loss of Crq in glia blocks this decrease in synapse numbers early in adulthood, it appears that glial cells are responsible for promoting early loss of synapses in the adult brain. Consistent with our observations, dynamic changes in synapses have been observed during this time window in response to changes in sensory input 6769 , and these have been shown to be regulated by the glial phagocytic receptor Drpr 70 .…”
Section: Discussionsupporting
confidence: 90%
“…Given that loss of Crq in glia blocks this decrease in synapse numbers early in adulthood, it appears that glial cells are responsible for promoting early loss of synapses in the adult brain. Consistent with our observations, dynamic changes in synapses have been observed during this time window in response to changes in sensory input 6769 , and these have been shown to be regulated by the glial phagocytic receptor Drpr 70 .…”
Section: Discussionsupporting
confidence: 90%
“…Finally, recent work has found that astrocytic MEGF10 is also responsible for thalamo-cortical synapse engulfment in ocular dominance plasticity (Lee et al, 2022). Thus, Draper/MEGF10-mediated signaling orchestrates temporally limited critical period pruning in multiple experimental models (Lee et al, 2022;Nelson et al, 2024).…”
Section: Discussionmentioning
confidence: 99%
“…Ensheathing glia extend processes into VM7 to perform critical period pruning in a Draper-dependent manner Draper is a highly conserved engulfment receptor, and its genetic requirement for synapse removal during critical period plasticity suggested the straightforward hypothesis (Nelson et al, 2024) that it mediates phagocytosis of Or42a OSN terminals by ensheathing glia. Before directly testing this, we investigated if ensheathing glial processes infiltrate VM7 following critical period EB exposure, and if so, whether this morphological change is Draper-dependent.…”
Section: Draper Is Required In Ensheathing Glia For the Elimination O...mentioning
confidence: 99%
See 1 more Smart Citation